ANALISIS FRAMING TERHADAP PEMBERITAAN COVID-19 DI OKEZONE.COM DAN CNNINDONESIA.COM - Fikry Zahria Emeraldien; Kinanti R. Hayati; El Haanim Nur Diny; Irvana Arum Sari Adiputro; Afifah Dwi Lestari (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
This study examines Covid-19 coverage in two online mass media in Indonesia, okezone.com and cnnindonesia.com 11-13 and 20 April 2022 editions. In this research, researchers used Zhongdang Pan and Gerald Kosicki's framing analysis by applying descriptive qualitative research methods in the form of news text from the two online mass media. From the results of this study, researchers found that Okezone.com media news framing refers more to negative news angles where they inform about the facts and dangers of Covid-19 without warning or anything like that. Meanwhile, CNNIndonesia.com's news framing is more positive and contains an appeal. Media CNNIndonesia.com is also more inclined towards the government but still trying to be objective. The information that this media presents seems to urge the public to remain calm, even though there are still positive cases every day. In conclusion, the two online media Okezone.com and CNNIndonesia.com are able to report about Covid-19 in a frame that educates the public regarding what is currently happening objectively. Keywords: Covid-19 news, Online Media, Framing Analysis, Pan and Kosicki.